Diagnosis- and Cell Type-Specific Mitochondrial Functional Pathway Signatures in Schizophrenia and Bipolar Disorder - Glausier, Jill R.; Enwright, John F.; Lewis, David A. (The American journal of psychiatry, 2020)
The shared risk factors and clinical features in schizophrenia and bipolar disorder may be linked via mitochondrial dysfunction. However, the severity of mitochondrial dysfunction, and/or the specific mitochondrial functional pathways affected, may differ between diagnoses, especially at the level of individual cell types. Transcriptomic profiling data for a gene set indexing mitochondrial functional pathways were obtained for dorsolateral prefrontal cortex (DLPFC) gray matter and layer 3 and layer 5 pyramidal neurons of subjects with schizophrenia or bipolar disorder. Analyses were conducted using a dual strategy: identification of differentially expressed genes (DEGs) and their functional pathway enrichment, and application of weighted gene coexpression network analysis. These analyses were repeated in monkeys chronically exposed to antipsychotic drugs to determine their effect on mitochondrial-related gene expression. In DLPFC gray matter, 41% of mitochondrial-related genes were differentially expressed in the schizophrenia group, whereas 8% were differentially expressed in the bipolar group. In the schizophrenia group, 83% of DEGs showed lower expression, and these were significantly enriched for three functional pathways, each indexing energy production. DEGs in the bipolar disorder group were not enriched for functional pathways. This disease-related pattern of findings was also identified in pyramidal neurons. None of the gene expression alterations disrupted coexpression modules, and DEGs were not attributable to antipsychotic medications. Schizophrenia and bipolar disorder do not appear to share similar mitochondrial alterations in the DLPFC. The selective and coordinated down-regulation of energy production genes in schizophrenia is consistent with the effects of chronic reductions in pyramidal neuron firing, and enhancement of this activity may serve as a therapeutic target.